Reward-based crowdfunding on the Polish market - Kędzierska- Szczepaniak, Angelika (Crowdfunding bazujący na nagrodach na rynku polskim, 2020)
The conditions for the functioning of enterprises, organizations, communities or even individuals have been changing with each passing year. Crowdfunding can become a way to meet the financial needs of the above-mentioned entities, especially when it may be difficult to obtain capital in a different way. This is challenging the traditional boundaries in social and economic aspects that have existed for centuries between industry, the financial sector and the public. Crowdfunding can be considered not only in terms of finance, economics or law, but also in sociology and psychology. The decisions of participants in crowdfunding projects are not always economically and rationally justified. Researchers are trying to find some regularities in projects realized on crowdfunding platforms all over the world, measuring the social and economic impact of crowdfunding. It can be hypothesized that crowdfunding transactions in Poland are characterized by their strong concentration. This may indicate the immaturity and high randomness of the crowdfunding market. The aim of the article is to analyze the projects implemented on the largest crowdfunding platform based on rewards in Poland
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 1, s. 89-100
Keywords: social financing; crowd-wisdom; crowdfunding platform; reward-based crowdfunding; finansowanie społecznościowe; mądrość tłumu; platforma crowdfundingowa; crowdfunding bonusowy